Countermeasures combined with thermosyphons against the thermal instability of high-grade highways in permafrost regions. (June 2020) - Yan, Zhongrui; Zhang, Mingyi; Lai, Yuanming; Pei, Wansheng; Luo, Tao; Yu, Fan; Yang, Sheng
Highlights: Cooling behavior of embankment models with two-phase closed thermosyphons was tested. Two-phase closed thermosyphon can effectively cool down the embankment center. Crushed-rock revetment can maintain the soil slope and slope toe frozen. Insulation prevents heat from entering into embankments in warm seasons. It could be helpful for optimizing construction of permafrost high-grade highway. Abstract: Permafrost degradation caused by climate warming and human activities would result in the thermal instability of embankments in permafrost regions, which would increase the maintenance cost. Two-phase closed thermosyphon (TPCT) is a widely-accepted green countermeasure against the problem in permafrost regions. However, the combination of TPCT with other countermeasures is usually proposed when it comes to a high-grade highway with a wide pavement. In order to explore the ideal combination, four combinations are compared by the instrumented physical embankment models: 1) inclined TPCT and insulation; 2) inclined TPCT, insulation and crushed-rock revetment; 3) L-shaped TPCT and insulation and 4) L-shaped TPCT, insulation and crushed-rock revetment. Under this experimental condition, the experimental results show that the TPCTs can effectively cool down the embankment center, the crushed-rock revetments can keep the soil slope and slope toe frozen during the whole freeze-thaw period after the 5th cycle, and the insulation can effectively prevent heat from entering into the embankment in warm seasons. After a thorough comparison of the thermal distribution and heat flux during seven freeze-thaw cycles, the embankment combined with L-shaped TPCT, insulation and crushed-rock revetment is proved to be the best way to keep the thermal stability of the wide-paved embankment. The results have potential to use for the future optimal construction against the thermal instability of high-grade highways in permafrost regions.